Induction of Hair Growth by Insulin-Like Growth Factor-1 in 1,763 MHz Radiofrequency-Irradiated Hair Follicle Cells - Yoon, Sun-Young (Public Library of Science, 2011)
Radiofrequency (RF) radiation does not transfer high energy to break the covalent bonds of macromolecules, but these low energy stimuli might be sufficient to induce molecular responses in a specific manner. We monitored the effect of 1,763 MHz RF radiation on cultured human dermal papilla cells (hDPCs) by evaluating changes in the expression of cytokines related to hair growth. The expression of insulin-like growth factor-1 (IGF-1) mRNA in hDPCs was significantly induced upon RF radiation at the specific absorption rate of 10 W/kg, which resulted in increased expression of B-cell chronic lymphocytic leukemia/lymphoma 2 (BCL-2) and cyclin D1 (CCND1) proteins and increased phosphorylation of MAPK1 protein. Exposure to 10 W/kg RF radiation 1 h per day for 7 days significantly enhanced hair shaft elongation in ex vivo hair organ cultures. In RF-exposed follicular matrix keratinocytes in the hair bulb, the expression of Ki-67 was increased, while the signal for terminal deoxynucleotidyl transferase dUTP nick end labeling was reduced. From these results, we suggest that 1,763 MHz RF exposure stimulates hair growth in vitro through the induction of IGF-1 in hDPCs.